Growth performance and lysozyme activity of rainbow trout fingerlings fed with vitamin E and selenium, marjoram (Origanum spp.), and ajwain (Trachyspermum ammi) extracts. Issue 1 (1st January 2018) - Ali, Mohsen; Soltanian, Siyavash; Akbary, Paria; Gholamhosseini, Amin
ABSTRACT: The aim of this study was to investigate the effects of vitamin E and selenium, marjoram ( Origanum spp.), and ajwain ( Trachyspermum ammi ) extracts on growth performance and lysozyme activity of rainbow trout fingerlings. The results of this study showed that adding ajwain (1%) and marjoram (2%) extracts and Vitamin E plus selenium (1%) significantly increased ( P  < .05) the growth factors compared to the control group in rainbow trout. In addition, the survival rate (SR) was 100% after applying the oxygen shock test on trout fed with 1% and 0.5% ajwain extract and 0.5% vitamin E plus Selenium supplement, which was significantly higher than other groups ( P  < .05). Another finding showed that 1% vitamin E plus selenium supplement and diets containing ajwain and marjoram at the level of 1% had significantly the highest value compared to other groups ( P  < .05). The measured total antibodies level showed that the groups 1% vitamin E plus Selenium supplement, 1% marjoram, and 1% and 2% ajwain, respectively, had the highest levels compared to the control group. It was shown in the present study that feeding rainbow trout fingerlings with 1% ajwain and marjoram extracts and vitamin E plus selenium as dietary supplements improved growth factor, lysozyme activity and SR.